A complementary examination of author characteristics of finance journals. Issue 4 (11th April 2016) - Chan, Kam C.; Wong, Annie; Wong, Hannah
Abstract : Purpose: – The purpose of this paper is to provide a complementary analysis of finance journals that are often being overlooked in prior studies. Specifically, the authors examine the Australian Business Dean Council's (ABDC's) C-ranked journals in terms of their authors' affiliations with US colleges, US colleges with Association to Advance Collegiate Schools of Business (AACSB) accreditations, and US colleges with AACSB doctoral program accreditations. Design/methodology/approach: – A list of C-ranked journals is downloaded from the ABDC's website. Full-text articles of these journals are downloaded from library databases for the five-year period of 2009-2013. Author affiliations are collected from the corresponding articles. Journal histories, journal editor locations, Cabell's journal rankings, and acceptance rates are collected from the ABDC's database, Cabell's Directory, journal websites, and library databases. The final sample consists of 28 finance journals. Findings: – The authors find that these journals have a substantial number and percentage of authors from US colleges. Among the US authors, about 92 percent of them are from AACSB accredited schools and most of them are from AACSB accredited schools with doctoral programs. The findings support the notion that these journals are important publication outlets for US researchers. The authors also find that journals with longer histories and US-based editors have a higher percentage of US authors. In addition, journals with better Cabell's journal rankings and higher rejection rates have higher percentage of US authors from AACSB accredited schools with doctoral programs. Originality/value: – C-ranked journals are often neglected in prior studies on journal characteristics because they are less well-known and less likely to be cited. However, these journals constitute as many as half of all finance journals in the ABDC database and can be important publication outlets for finance researchers. This study contributes to the literature by examining the author characteristics of these journals, namely, the proportions of authors who come from US colleges and authors who come from AACSB accredited US programs. Such an analysis will provide valuable insight into the value of these journals.